Factors that predict progression of von Hippel-Lindau disease-related malignancy: a longitudinal cohort study - Jae Ho Lee; Hyun Young Lee; Ji Eun Park; Min-Ju Kim; Dae Wook Hwang; Sangjoon Chong; Moinay Kim; Joo Yong Lee; Cheryn Song; Beom Hee Lee (BMC Cancer)
Abstract Background Von Hippel-Lindau (vHL) disease encompasses various genetic subtypes with poorly defined progression patterns. This retrospective study of a longitudinal cohort aimed to characterize follow-up duration, treatment rates, and progression patterns according to genomic subtype, and to identify risk factors for progression. Methods Between June 2003 and June 2020, the study enrolled 94 patients (mean age, 37.1 years; 49 females; 84 with missense mutations and 10 with truncating (i.e., insertion/deletion) mutations in the VHL tumor suppressor gene). MRI and CT imaging data were analyzed to compare tumor incidence between the two mutation groups. Cox regression analysis was used to assess predictors of hemangioblastoma (Hb) and renal cell carcinoma (RCC) progression based on genetic subtype, tumor volume, and clinical characteristics. Results Patients with missense mutations were more often treated for RCC (p = 0.013) and adrenal pheochromocytoma (p < 0.001) than those with truncating mutations; however, genetic subtype was not a significant predictor of time-to-progression of Hb or RCC. Larger tumor volume at baseline was an independent predictor of Hb progression (HR, 1.029; 95% CI, 1.013–1.046; p < 0.001) and RCC (HR, 1.011; 95% CI, 1.005–1.017; p < 0.001). Male sex was also an independent predictor of RCC progression (HR, 3.368; 95% CI, 1.351–8.396; p = 0.009). Conclusions Genetic subtype was not associated with progression of vHL disease, but missense mutations were associated with higher treatment rates for RCC and adrenal pheochromocytoma. The finding that progression of Hb and RCC is linked to larger baseline tumor volume and male sex may facilitate clinical management.